Plant cell polarity: the ins-and-outs of sterol transport. - Betts, H; Moore, I (2003)
Plant cells and tissues develop polarities essential for completion of development. Recent studies highlight the important role of membrane sterols in plant cell polarity and suggest that sterols may influence the dynamic trafficking of proteins with polar distributions in the plasma membrane.